HOMO SACER ORANG PEGATEN DALAM NOVEL KUBAH KARYA AHMAD TOHARI (PERSPEKTIF GIORGIO AGAMBEN) - Pratiwi, Wista Ayu; Apriyani, Tristanti (Universitas Ahmad Dahlan, 2020)
Ahmad Tohari is a writer who created a novel based on the historical events of his people. One of Ahmad Tohari's novels which is the focus of this research study is the Kubah novel. The involvement of Karman in the communist party turned out to change his life. Referring to the formulation of Giorgio Agamben (1998) about modern biopolitics, the depiction of the life of the character Karman in the Kubah novel, is very much in accordance with the concept of Homo sacer and bare lofe proposed by Agamben. By using descriptive analysis methods, this study aims to analyze the concepts of bare life and homo sacers which are reflected in the Karman character in Ahmad Tohari's Kubah novel. Karman figure becomes a homo sacer who has an identity as a pegaten hamlet resident, but he feels he does not get his rights as a hamlet resident. The change in Karman's self as an innocent, religious and devout individual, until becoming an atheist, was a process of bare life.Â Â